Penelitian Pembuatan Formulasi Pestisida Bentuk Bubuk Yang Dapat Disuspensikan (Wettable Powder) Dari Bahan Lokal - Hendartini Hendartini (Balai Besar Kimia dan Kemasan, 1987)
Of all the conventional types of pesticide formulation, the manufacture of wettable powder is perhaps the most difficult. It needs the science and the skill to convert an organik toxicants into products that comply with standardformulation specification. However, by carefull choise of carrier, adjusvants, and processing technique, a satisfactory formulation can be achieved. Seven types of wettable powder formulation using local ingredient that differ in concentration of adjuvant were prepared in this experiment. The physico-chemical test showed that the best result is formulation E which contain MIPC 52%, kaolin 43%, wetting agent 2 %, and suspensing agent 3 %, but the suspensibility is not comply with F AO spesification.